Stellaria media attenuates the hyperglycemia and hyperlipidemia in alloxan-induced diabetic rat - Khan, Rahmat; Ahmad, Wasim; Ahmed, Mushtaq (Bangladesh Journal of Pharmacology, 2019)
Abstract The objective of this research work was to assess the hyperglycemic and hyperlipidemiceffects of Stellaria media in alloxan induced diabetic rats using different experimental models. Standard documented protocols were used to concede the in vitro and in vivo activities. Biochemical markers studies were also done. The results of the study showed strong pancreatic α-amylase and β-glucosidase inhibition in-vitroat varying concentrations of the extract which further validated the in-vivo anti-diabetic action of the plant because of the inhibition of the above enzymes.The administration of various concentrations of the extract showedmomentous decrease in fasting blood level when compared to diabetic control. Similarly, remarkably improved hemoglobin (+20.10%), and decreased HbA1c (−48.44%) was observed when compared to diabetic control rats. The extract also caused reduced serum enzyme (ALT, ALP, bilirubin) levels and produced a succeeding recovery toward their normal values.It can be concluded from these investigations that the in-vitro and in-vivo hypoglycemic and hypolipidemic activity offers the methodicaljustification for the use of S. media in herb based anti-diabetic treatment. Video Clip of Methodology: Alpha-amylase inhibitory activity: 14 min 17 sec: Click to watch